2017
DOI: 10.1111/cbdd.12916
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into the antiprion compound inhibition mechanism of native prion folding over misfolding

Abstract: Transition of a physiological folded prion (PrP ) into a pathogenic misfolded prion (PrP ) causes lethal neurodegenerative disorders and prion diseases. Antiprion compounds have been developed to prevent this conversion; however, their mechanism of action remains unclear. Recently, we reported two antiprion compounds, BMD29 and BMD35, identified by in silico and in vitro screening. In this study, we used extensive explicit-solvent molecular dynamics simulations to investigate ligand-binding inhibition by antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In a previous study, we reported that the hotspot regions in β1 (Asn159), α2 (Val189, Tyr192, and Lys194), and the α1~α2 loop (Glu196), which are involved in the pathogenic conversion process, are obstructed by binding to the anti-prion compounds. In particular, the α1~α2 salt bridge between Arg156 and Glu196 of the misfolded PrP C returns to the PrP C state in the presence of BMD42-29 [27]; this finding is consistent with other reports [39,47]. BMD42-2910 has hydrogen bonding interactions at Glu196, which are not absent in BMD42-29.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a previous study, we reported that the hotspot regions in β1 (Asn159), α2 (Val189, Tyr192, and Lys194), and the α1~α2 loop (Glu196), which are involved in the pathogenic conversion process, are obstructed by binding to the anti-prion compounds. In particular, the α1~α2 salt bridge between Arg156 and Glu196 of the misfolded PrP C returns to the PrP C state in the presence of BMD42-29 [27]; this finding is consistent with other reports [39,47]. BMD42-2910 has hydrogen bonding interactions at Glu196, which are not absent in BMD42-29.…”
Section: Discussionsupporting
confidence: 90%
“…These aggregates can be detected by western blotting and inhibited by anti-PrP compounds [26]. Additionally, the structural mechanisms of BMD42-29 inhibition have been studied [27]. In the present study, we extended previous research by designing the derivatives of BMD42-29 using in silico feedback, specifically with chemical modifications based on docking pose of BMD42-29; the aim was to elucidate the improved anti-prion activity compared to that achieved by a previous procedure [25].…”
Section: Introductionmentioning
confidence: 90%
“… 21 , who proposed one compound, named GN8, which strongly stabilises normal conformation by binding to PrP C . Based on several computational studies, the specific binding site of PrP C can be specified as Asn159, Val189, Thr192, Lys194, and Glu196 15 , 22 , 23 . Therefore, focusing on the hotspot pocket as the interaction site between GN8 and PrP C may be a promising way to develop new antiprion drugs in the future.…”
Section: Introductionmentioning
confidence: 99%